Employee Satisfaction vs. Employee Engagement vs. Employee NPS - Yaneva, Maya (European Journal of Economics and Business Studies, 2018)
Human Resources are key for the success of business organizations. The science is focusing on Human Resources Management in times when technical resources are rapidly developing and significantly changing the working environment. The requirements toward the human resources are evolving as well. At the same time, the expectations of the candidates toward the employers are getting more demanding in terms of working conditions and appreciation. Employee profiles and change management are key aspects of HR management while the companies are striving to adjust their learning and development programs, working environment and structures in order to retain and develop their associates. Companies start to measure their employees’ satisfaction, than converting to employee engagement and nowadays more and more organizations are focusing on employee NPS (net promoter score), which is not only promoting the products or services of the company they are engaged in, but also the company as an employer. This paper is focusing on employee satisfaction, employee engagement and eNPS (employee net promoter score). It gives guidance what are the global trends with local impact, presenting results from several surveys on the Bulgarian market of global and local companies executed between 2012 and 2017. The primary focus of the research is to outline which channels and ways of communications are the most beneficial in the attempts of the business organizations to address their employees, boost their enjoyment and motivation and make them ambassadors of the product and services they produce, but also promote them as an employer. Presenting the outcome of the surveys is giving guidance on top drivers for employee satisfaction, engagement and loyalty. It is leading to conclusions that are enlightening the associates’ interpretation of those drivers in the different contexts of business environment. The organizations are conducting internal surveys within their global structures, but also participating in researches on the local market in Bulgaria to cross check the findings and the trends. Local cultural differences are influencing the organizational culture and trends of the business. The paper analyses the results related to the Bulgarian market and provides further recommendations as to how to address the findings resulting from the survey.
Keywords: employee satisfaction, employee engagement, employee NPS, net promoter score, communication, human resources, employee retention